Political wisdom of the Kajang "Ammatoa" indigenous community in South Sulawesi - Latief, Iqbal; Syam, Ridwan (ETNOSIA : Jurnal Etnografi Indonesia, 2022)
Democracy, which is implemented in Indonesia through general elections (Elections), places the community as a whole as the holder of people's sovereignty.  This is guaranteed in the 1945 Constitution of the Republic of Indonesia (UUD).  However, the implementation of people's sovereignty is still a problem, because there is still a low understanding of the people's sovereignty that they have, especially in elections.  One component of society that also has political sovereignty is indigenous communities, especially in South Sulawesi, namely the Kajang "Ammatoa" indigenous community. Therefore, this study examines the meaning of political sovereignty in the Kajang indigenous community "Ammatoa" and the local wisdom owned and implemented in the 2019 elections, including the 2020 Regional Head Election (Pilkada) in Bulukumba Regency. The method used is descriptive qualitative, and the processed data is primary and secondary. This research begins with the identification and formulation of problems, data collection, data processing, and analysis, including data classification and reduction, drawing conclusions, and verification. The results of this study; (1) Although the Kajang indigenous community is closed, the application of democratic values has been realized for a long time and has become its main local wisdom in choosing leaders called "ammatoa" (traditional chairmen). That is, "ammatoa" is democratically elected and not because of the principle of blood or hereditary ties (traditional leadership); (2) The meaning of democracy and political wisdom, also expressed in elections and regional elections, "ammatoa" as a leader gives freedom to its citizens to choose according to their beliefs without any intervention. So, even though there are "ammatoa" children who became Caleg in the 2019 elections, they were not elected; (3) responsibility as a citizen is also evident in the high level of participation of the Kajang indigenous community in elections and regional elections, even though initially there were cultural and administrative obstacles. This proves that the Kajang indigenous community has practiced the meaning of popular sovereignty for a long time and has become a form of political wisdom. As a suggestion, it is necessary to make a follow-up study that captures the meaning of people's sovereignty in other indigenous communities as a reference in formulating inclusive election policies in Indonesia.